PKM pembuatan asesori untuk ibu rumah tangga petani dan remaja putri putus sekolah dari limbah kain perca tukang jahit - Asiani Abu; Rahmansah Rahmansah (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Community Service (PKM) is 1) Providing counseling to partners about the use, benefits, and economic value of souvenirs / accessories made from raw materials for sewing sewing patchwork. 2) Introducing the materials and tools used to make souvenirs / sewing accessories raw materials for sewing tailors. 3) Training and assisting partners to make various patterns of souvenirs / sewing accessories for broken sewing materials. 4) Training and assisting partners in making various kinds of souvenirs. / accessories that have economic value, from the main raw material for sewing sewing patchwork. The External Target is to Produce souvenirs / accessories made from the main raw material for sewing sewing cloth, which is a beautiful brooch and can be worn on mothers and teenage girls, at weddings, birthday parties, and similar parties. The method used is: lecture, discussion, question and answer, and demonstration. The results achieved by community service are 1). Being equipped with the skills to make brooches and key chains 2) Generating confidence in the trainees who are gifted in the skills of souvenirs / accessories for making brooches 3) Are cadres who can pass on their knowledge and skills to their friends who have not received training. 4). Trainees who still don't know anything about how to use patchwork, can find out how to make brooches